2010
DOI: 10.1038/nrclinonc.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Complete molecular response in CML after p210 BCR–ABL1-derived peptide vaccination

Abstract: The patient was treated with a target immune approach receiving a therapeutic vaccine that consisted of an immunogenic 25-mer b2a2 breakpoint-derived peptide (CMLb2a2-25) with binding properties for several HLA-DR molecules. After nine boosts of vaccine the patient developed an adequate b2a2-25 peptide-specific CD4(+) T-cell response and BCR-ABL1 transcript started to decline in peripheral blood. No hematological or extrahematological effects were documented during therapy. At the last evaluation, 39 months si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Most immune reactivities found after DLI against any of these antigens are weak. Moreover, immune reactivity against autologous antigens is frequently suppressed by mechanisms of tolerance mediated by, e.g., regulatory T-cells (Tregs) or inhibitory cytokines (104). Peptides presented by foreign HLA antigens can be immunogenic by different configurations (105).…”
Section: Improvement Of the Responsementioning
confidence: 99%
“…Most immune reactivities found after DLI against any of these antigens are weak. Moreover, immune reactivity against autologous antigens is frequently suppressed by mechanisms of tolerance mediated by, e.g., regulatory T-cells (Tregs) or inhibitory cytokines (104). Peptides presented by foreign HLA antigens can be immunogenic by different configurations (105).…”
Section: Improvement Of the Responsementioning
confidence: 99%
“…116 Larger observational studies of junctional peptide vaccination of chronic phase CML patients on imatinib (www.clinicaltrials.gov identifier NCT00466726) have demonstrated T-cell responses and reductions in BCR-ABL1 transcripts in vaccine recipients, 117119 whereas sustained CMRs in the absence of TKI therapy have been reported in a few vaccinated patients. 120,121 …”
Section: Immunological Approaches To CML Stem Cell Eradicationmentioning
confidence: 99%
“…The role of the patient's own immune system in recognizing BCR-ABL-expressing cells, and whether this can be boosted for beneficial effect, is currently under investigation in vaccination studies, although no convincing results have been reported. 7,8 Similarly, it is not known whether immune recognition by the patient's immune system is playing a part in maintaining remission of nonrelapsing patients in whom TKI treatment is discontinued.…”
Section: Introductionmentioning
confidence: 99%